Studying and Analyzing the Current Situation of Integrating BIM Technology in Engineering Education in Syrian Universities - سعود لما (Latakia University Journal -Engineering Sciences Series, 2024)
Building Information Modeling (BIM) technology is one of the latest technologies in the construction industry, and has proven to be very useful in improving the quality of engineering project work. Because of the great role that BIM technology plays in the construction industry and the increasing spread of this technology globally, many universities around the world have begun to integrate BIM into their programs and curricula for architecture and construction engineering (AEC). This integration aims to meet the increasing demand from the labor market to prepare engineers who are proficient in this technology. Despite the global interest in integrating BIM in education, the interest in Syrian universities was limited to some individual efforts by faculty members and some external courses to use BIM programs. Through this research, we aim to study and analyze the current situation of engineering colleges in three areas of initiatives and procedures of the educational institution about BIM, educational process and technological capabilities. A questionnaire was developed and data were collected from 26 faculties of civil and architectural engineering in Syrian public and private universities. The data was analyzed and a set of recommendations were produced aimed at improving the reality of BIM in engineering colleges and highlighting the challenges that prevent this.